2023
DOI: 10.3389/fcvm.2023.1172005
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage occlusion in the absence of intraprocedural product specialist monitoring: is it time to proceed alone? Results from a multicenter real-world experience

Abstract: BackgroundPercutaneous left atrial appendage occlusion (LAAO) presents many technical complex features, and it is often performed under the intraprocedural surveillance of a product specialist (PS). Our aim is to assess whether LAAO is equally safe and effective when performed in high-volume centers without PS support.MethodsIntraprocedural results and long-term outcome were retrospectively assessed in 247 patients who underwent LAAO without intraprocedural PS monitoring between January 2013 and January 2022 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Margonato et al 59 reported that LAAC was equally safe and effective without PS support according to their real-world experience.…”
Section: Laac In the Absence Of Intraprocedural Product Specialist Mo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Margonato et al 59 reported that LAAC was equally safe and effective without PS support according to their real-world experience.…”
Section: Laac In the Absence Of Intraprocedural Product Specialist Mo...mentioning
confidence: 99%
“…As COVID‐19 pandemic has raised the issue of limited access of nonhospital staff to operative rooms, different procedures without the help of the product specialist (PS) have been performed. Margonato et al 59 . reported that LAAC was equally safe and effective without PS support according to their real‐world experience.…”
Section: Remaining Challenges and Future Directionsmentioning
confidence: 99%